Pretty People : Movie Stars of the 1990s - Everett, Anna, 1954- (Book collections on Project MUSE., 2012)
In the 1990s, American civil society got upended and reordered as many social, cultural, political, and economic institutions were changed forever. Pretty People examines a wide range of Hollywood icons who reflect how stardom in that decade was transformed as the nation itself, signaling significant changes to familiar ideas about gender, race, ethnicity, age, class, sexuality, and nationality.